Species life‐history strategies affect population responses to temperature and land‐cover changes - Albaladejo‐Robles, Gonzalo; Böhm, Monika; Newbold, Tim (Global change biology, 2023)
Human‐induced environmental changes have a direct impact on species populations, with some species experiencing declines while others display population growth. Understanding why and how species populations respond differently to environmental changes is fundamental to mitigate and predict future biodiversity changes. Theoretically, species life‐history strategies are key determinants shaping the response of populations to environmental impacts. Despite this, the association between species life histories and the response of populations to environmental changes has not been tested. In this study, we analysed the effects of recent land‐cover and temperature changes on rates of population change of 1,072 populations recorded in the Living Planet Database. We selected populations with at least 5 yearly consecutive records (after imputation of missing population estimates) between 1992 and 2016, and for which we achieved high population imputation accuracy (in the cases where missing values had to be imputed). These populations were distributed across 553 different locations and included 461 terrestrial amniote vertebrate species (273 birds, 137 mammals, and 51 reptiles) with different life‐history strategies. We showed that populations of fast‐lived species inhabiting areas that have experienced recent expansion of cropland or bare soil present positive populations trends on average, whereas slow‐lived species display negative population trends. Although these findings support previous hypotheses that fast‐lived species are better adapted to recover their populations after an environmental perturbation, the sensitivity analysis revealed that model outcomes are strongly influenced by the addition or exclusion of populations with extreme rates of change. Therefore, the results should be interpreted with caution. With climate and land‐use changes likely to increase in the future, establishing clear links between species characteristics and responses to these threats is fundamental for designing and conducting conservation actions. The results of this study can aid in evaluating population sensitivity, assessing the likely conservation status of species with poor data coverage, and predicting future scenarios of biodiversity change. In this work, we showed how fast‐lived species populations present positive population growth rates in areas that have experienced recent temperature and land‐use changes. Whereas populations of slow‐lived species showed the opposite response.